A note on the use of optimal control on a discrete time model of influenza dynamics - Paula A. González-Parra; Sunmi Lee; Leticia Velázquez; Carlos Castillo-Chavez (Mathematical Biosciences and Engineering)
A discrete time Susceptible - Asymptomatic - Infectious - Treated - Recovered (SAITR) model is introduced in the context of influenza transmission.We evaluate the potential effect of control measures such as social distancing and antiviral treatment on the dynamics of a single outbreak.Optimal control theory is applied to identify the best way of reducing morbidity and mortality at a minimal cost. The problem is solved by using a discrete version of Pontryagin's maximum principle. Numerical results show that dual strategies have stronger impact in the reduction of the final epidemic size.